2018
DOI: 10.3390/s18093089
|View full text |Cite
|
Sign up to set email alerts
|

Precision and Accuracy of a Direct-Reading Miniaturized Monitor in PM2.5 Exposure Assessment

Abstract: The aim of this study was to evaluate the precision, accuracy, practicality, and potential uses of a PM2.5 miniaturized monitor (MM) in exposure assessment. These monitors (AirBeam, HabitatMap) were compared with the widely used direct-reading particulate matter monitors and a gravimetric reference method for PM2.5. Instruments were tested during 20 monitoring sessions that were subdivided in two different seasons to evaluate the performance of sensors across various environmental and meteorological conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 57 publications
(93 reference statements)
0
44
0
Order By: Relevance
“…In addition, 19 projects evaluating OEMs, SSys, or both, and reporting quantitative comparisons of LCS data and reference measurements were identified. They include the Air Quality Egg, Air Quality Station, AirCasting [19,[35][36][37], Carnegie Mellon [36,38], CitiSense [30], Cairsense [39], Developer Kit [19], HKEPD/14-02771 [40], making-sense.eu [41], communitysensing.org [32], MacPoll.eu [20], OpenSense II [42,43], Proof of Concept AirSensEUR [22], and SNAQ Heathrow [44,45]. Out of the 1423 records collected from literature, we identified 1188 records (197 OEMs and 991 SSys) from 89 alive LCS (24 OEMs and 65 SSys) and 235 records (123 OEMs and 112 SSys) from 23 "non active" (or discontinued) LCS (7 OEMs and 16 SSys).…”
Section: Classification Of Low-cost Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 19 projects evaluating OEMs, SSys, or both, and reporting quantitative comparisons of LCS data and reference measurements were identified. They include the Air Quality Egg, Air Quality Station, AirCasting [19,[35][36][37], Carnegie Mellon [36,38], CitiSense [30], Cairsense [39], Developer Kit [19], HKEPD/14-02771 [40], making-sense.eu [41], communitysensing.org [32], MacPoll.eu [20], OpenSense II [42,43], Proof of Concept AirSensEUR [22], and SNAQ Heathrow [44,45]. Out of the 1423 records collected from literature, we identified 1188 records (197 OEMs and 991 SSys) from 89 alive LCS (24 OEMs and 65 SSys) and 235 records (123 OEMs and 112 SSys) from 23 "non active" (or discontinued) LCS (7 OEMs and 16 SSys).…”
Section: Classification Of Low-cost Sensorsmentioning
confidence: 99%
“…Those devices are manufactured in emerging economies, such as the Republic of China and the Republic of Korea [50]. Some of these LCS can achieve similar performance to more expensive OEMs [18,19,[29][30][31]37,48,49,[51][52][53][54][55][56].…”
Section: Classification Of Low-cost Sensorsmentioning
confidence: 99%
“…Different principles of operation were under discussion to be applied as particle number detectors [4]. The most commonly used PM sensors, such as those in ambient air monitoring [28,29], exposure assessment [30][31][32][33][34], vehicle cabin air quality [35], or even filter monitoring in diesel exhaust [36][37][38], were not applicable to vehicle exhaust due to their relatively large lower size, high detection limit, or slow response time. Currently, there are two concepts for the particle sensors (detectors) inside the on-board systems: condensation particle counters (CPCs), similar to those in laboratory systems, and advanced diffusion chargers (DCs) [4,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…However, several recent environmental field investigations have showed that although these miniaturized monitors have good reliability, they are only moderately correlated with reference measures and tend to be biased with increasing PM 2.5 concentrations. 21,22 The best solution for future research to overcome this limitation might be to conduct trials as close to the DEQ monitors as possible.…”
Section: Some Of the Logistical Challenges Led To Study Limitationsmentioning
confidence: 99%